Quality of Red Blood Cells Isolated from Umbilical Cord Blood Stored at Room Temperature. (19th January 2012) - Zhurova, Mariia; Akabutu, John; Acker, Jason
Abstract : Red blood cells (RBCs) from cord blood contain fetal hemoglobin that is predominant in newborns and, therefore, may be more appropriate for neonatal transfusions than currently transfused adult RBCs. Post-collection, cord blood can be stored at room temperature for several days before it is processed for stem cells isolation, with little known about how these conditions affect currently discarded RBCs. The present study examined the effect of the duration cord blood spent at room temperature and other cord blood characteristics on cord RBC quality. RBCs were tested immediately after their isolation from cord blood using a broad panel of quality assays. No significant decrease in cord RBC quality was observed during the first 65 hours of storage at room temperature. The ratio of cord blood to anticoagulant was associated with RBC quality and needs to be optimized in future. This knowledge will assist in future development of cord RBC transfusion product.